Sequence polymorphisms in ribosomal RNA genes and variations in chromosomal loci of Oenothera odorata and O. laciniata - Seo, Jun Hyung; Bae, Hyo Geun; Park, Da Hee; Kim, Beom Seok; Lee, Jong Wook; Lee, Jung In; Kim, Dong Hyun; Lee, Seok Won; Seo, Bong Bo (Genes & genomics, 2013)
Numerous studies on Oenothera species have been investigated for the physiological and ecological characteristics. However, no such an information based on molecular cytogenetic has yet been introduced, in turn, is very essential for identifying sequence polymorphisms of rRNA genes with their loci on mitotic phases for further biological researches. In this study, sequence variations of rRNA genes in Oenothera odorata and O. laciniata were examined to identify informative factors as unique or repeat sequences in intra- and inter-specific variations. Intra-specific variation revealed that the sequences of the rRNA genes including the spacer regions were highly conserved revealing only a few variations. From the inter-specific variation, spacer regions of species were completely different as (1) non-homologous sequences in NTS and (2) different type repeat sequences in ITS 1, 2 and 5.8S rRNA, whereas the remaining coding regions were highly conserved. FISH was carried out on mitotic phases using the 5S rDNA of the analyzed sequences. From the interphase and metaphase chromosomes of the examined species, two loci of 5S rDNA in O. odorata and four loci in O. laciniata were confirmed on the telomeric region of the short arm. Due to the small size and unclear centromere of the chromosomes, karyotype could not be completed. However, we confirmed that the chromosomes are organized by meta- and acrocentric chromosomes and the chromosomes with identified loci were assumed to be paired by the location of loci at the telomeric region on the short arm with relative lengths.